INCREASING KNOWLEDGE ABOUT DENTAL AND ORAL HEALTH AMONG POSYANDU CADRE IN CIBEUREUM HEALTH CENTER INDONESIA - Himawati, Marlin; Yulitasari, Triani; Selindion, Shelvi; Daffa Fauzana, Farhan (Fakultas Kedokteran Gigi Unjani, 2024)
Posyandu cadres have an important role in promotional efforts, namely providing counseling to visitors to the Posyandu community. The purpose of the research is to evaluate the knowledge and skills of dental health cadres in conducting early detection of dental and oral diseases so they can refer and actively participate in improving dental and oral health. The training was carried out through the presentation of material to dental health cadres in the Cibeureum area. Some of the educational media used are educational power points via zoom meetings. In this study, quasi experiment pretest and posttest design were carried out, and the research data was analyzed using a non-parametric paired sample test. The study was conducted on 35 cadres of Posyandu in the Cibeureum area. There was a significant difference between the pre-and post-training scores, with a p-value of 0.002. The counselling and education program for Posyandu cadres in the Cibeureum area has proven to be effective in increasing cadre knowledge. It is hoped that from the program, cadres can actively participate in community dental health unit activities. DOI : 10.54052/jhds.v4n2.p203-210